Estrategias gerenciales para el cumplimiento de normas y procedimientos en los protocolos de bioseguridad, Centro de Salud tipo C, cantón Tosagua - Carrión Benavides, Dayeni Johanna (2026)
The general objective of this research was to evaluate management strategies for compliance with standards and procedures in biosafety protocols at the Type C Health Center in Tosagua canton. A qualitative methodology with a descriptive approach was applied, complemented by inductive, deductive, and analytical-synthetic methods. The techniques used included interviews with the general management and surveys administered to healthcare personnel. The results show that the health center has an updated institutional protocol in accordance with the guidelines of the Ministry of Public Health, whose implementation is periodically verified. An adequate appropriation of the protocol was demonstrated by the personnel through theoretical and practical training, both in-person and virtual, and the use of digital tools such as Zimbra. The center has a supply management system that allows for the replenishment of personal protective equipment, although it faces budgetary constraints and administrative delays. However, supplies have been maintained. With the diagnosis made, an improvement plan was proposed. It was ultimately concluded that, although the center has made progress in implementing biosafety measures, there are still structural and management aspects that require improvement.